Adaptive social impact management for conservation and environmental management. Issue 2 (24th October 2017) - Kaplan‐Hallam, Maery; Bennett, Nathan J.
Abstract: Concerns about the social consequences of conservation have spurred increased attention the monitoring and evaluation of the social impacts of conservation projects. This has resulted in a growing body of research that demonstrates how conservation can produce both positive and negative social, economic, cultural, health, and governance consequences for local communities. Yet, the results of social monitoring efforts are seldom applied to adaptively manage conservation projects. Greater attention is needed to incorporating the results of social impact assessments in long‐term conservation management to minimize negative social consequences and maximize social benefits. We bring together insights from social impact assessment, adaptive management, social learning, knowledge coproduction, cross‐scale governance, and environmental planning to propose a definition and framework for adaptive social impact management (ASIM). We define ASIM as the cyclical process of monitoring and adaptively managing social impacts over the life‐span of an initiative through the 4 stages of profiling, learning, planning, and implementing. We outline 14 steps associated with the 4 stages of the ASIM cycle and provide guidance and potential methods for social‐indicator development, predictive assessments of social impacts, monitoring and evaluation, communication of results, and identification and prioritization of management responses. Successful ASIM will be aided by engaging with best practices – including local engagement and collaboration in the process, transparent communication of results to stakeholders, collective deliberation on and choice of interventions, documentation of shared learning at the site level, and the scaling up of insights to inform higher‐level conservation policies‐to increase accountability, trust, and perceived legitimacy among stakeholders. The ASIM process is broadly applicable to conservation, environmental management, and development initiatives at various scales and in different contexts. Abstract : Article impact statement : Adaptive management of the social impacts of conservation will improve outcomes for local people and increase conservation effectiveness.